The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1590/s0103-21002011000200014
|View full text |Cite
|
Sign up to set email alerts
|

Motivo de retirada do cateter de Hickman em pacientes submetidos ao transplante de células-tronco hematopoéticas

Abstract: Objective: To identify rationale for removal of the first Hickman catheter implanted in patients undergoing allogeneic hematopoietic stem cell transplantation, the micro-organisms involved in the occurrence of infection, and the length of time the catheter was in situ. Methods: A cross sectional, retrospective study was conducted. The sample consisted of 57 transplant recipients. To conduct chart review, an instrument was developed containing variables related to patient identification, time of catheter use, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
11

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 16 publications
0
2
0
11
Order By: Relevance
“…The investigator evaluated local cutaneous effects on the skin in contact with the CIGD; assessed through skin evaluation immediately after each dressing removal to detect skin integrity, color abnormalities, or the presence of skin lesions. A retrospective cross-sectional study conducted at the same hospital and care unit in 2011 analyzed patients submitted to allogeneic HSCT that used tunneled catheters and showed that the mean permanence of the catheter was 45 days [25]. Based on this study, we followed the patients for 45 days.…”
Section: Methodsmentioning
confidence: 99%
“…The investigator evaluated local cutaneous effects on the skin in contact with the CIGD; assessed through skin evaluation immediately after each dressing removal to detect skin integrity, color abnormalities, or the presence of skin lesions. A retrospective cross-sectional study conducted at the same hospital and care unit in 2011 analyzed patients submitted to allogeneic HSCT that used tunneled catheters and showed that the mean permanence of the catheter was 45 days [25]. Based on this study, we followed the patients for 45 days.…”
Section: Methodsmentioning
confidence: 99%
“…Em relação ao tempo de enxertia da medula, é variável e, neste período, o paciente encontra-se exposto a uma etapa de profunda neutropenia e imunodeficiência, significativamente responsável por intercorrências infecciosas pós-transplante, principalmente na modalidade alogênica (3) . Ressalta-se que, antes de iniciar o tratamento, todos os pacientes necessitam inserir um Cateter Venoso Central (CVC), o qual, apesar de fundamental diante das necessidades do tratamento, representa um potencial fator de risco para o desenvolvimento de infecções, que constituem as principais causas de sua remoção (4)(5) . A infecção do cateter é uma complicação que pode acarretar prolongamento da internação do paciente, aumento da morbimortalidade, além da elevação dos custos de hospitalização (6) .…”
Section: Introductionunclassified
“…Esses dados vão de encontro aos apresentados em outros estudos desenvolvidos com pacientes adultos submetidos ao TCTH alogênico, nos quais a porcentagem de homens variou de 56,52 a 63% (BRAGA, 2011;CASTANHO et al, 2011;LEE et al, 2011;PEREIRA et al, 2013).…”
Section: Discussionunclassified
“…Sobre a idade dos sujeitos, os dados também corroboram com a literatura no que tange à variação, que foi de 16 a 67 anos, e também à média, que foi de 36 a 39,5 anos nos estudos consultados (BRAGA, 2011;CASTANHO et al, 2011;GERULL et al, 2011;LEE et al, 2011;PEREIRA et al, 2013).…”
Section: Discussionunclassified
See 1 more Smart Citation